Design and Development of the Information System for the Support of Human Resources - I. Ishmuradova, Izida; N. Karame, Anton; M. Sultanova, Aisylu; M. Ishmurad, Alfiya (International Journal of Engineering and Technology, 2018)
The type of information system depends on whose interests it serves and at what level of management. According to the nature of the concept and the logical organization of stored information, informative concepts are divided into factual, actual, geoinformational [1].Numerous large firms in the US and Europe have switched to the use of ERP information systems several years ago.The relevance of this project is that the development of an information system that is aimed specifically at the activities of the CJSC Muslumovsk serving several collective farms building organizations will enable the automated recording of the activities of the enterprise, accelerate the processing of documents, systematize the work with employees and will be aimed at automating and improving the work of the enterprise by example subsystem "Managing staffing".Â Â